Uric acid metabolism in the Dalmatian coach hound - Briggs, Oliver Martin (Division of Chemical Pathology, 2018)
The Dalmatian coach hound, when compared to other dog breeds, exhibits three characteristic abnormalities of uric acid metabolism, namely hyperuricaemia, hyperuricosuria and increased renal uric acid clearance. These properties are associated with hypoallantoinaemia and hypoallantoinuria. A result of these abnormalities is a high incidence of urate urolithiasis in this breed. Other diseases such as recurrent dermatitis, chronic cystitis and deafness are also found in the Dalmatian and whether there is any causal relationship with the uric acid disorder is unknown. In terms of the quantity of uric acid excreted, the Dalmatian dog resembles man more closely than the non-Dalmatian. On the other hand, in its high renal urate clearance, this breed of dogs differs from man, whose renal clearance values are lower and therefore closer to those of the non-Dalmatian. In this respect the Dalmatian resembles man affected with the inborn renal urate transport defect of renal hypouricaemia. The significance of uric acid metabolism in the Dalmatian has attracted many investigators in search of the underlying metabolic defect(s). Study of the Dalmatian may also be relevant to the understanding of disorders of purine metabolism in man for example hyperuricosuria, uric acid urolithiasis and hereditary renal hypouricaemia.